Аппроксимация формы импульсных электромагнитных воздействий биэкспоненциальной функцией - Петков, Александр Александрович (НТУ "ХПИ", 2005)
In work the general technique of the decision of the problem of a deviations mini-mization experimental data which describing pulse electromagnetic processes, from values of the biexponential function approximating these data is offered
Keywords: форма воздействия; электромагнитное воздействие; биэкспоненциальная функция